Primary endothelial cell–specific regulation of hypoxia‐inducible factor (HIF)‐1 and HIF‐2 and their target gene expression profiles during hypoxia. Issue 7 (27th March 2019) - Bartoszewski, Rafal; Moszyńska, Adrianna; Serocki, Marcin; Cabaj, Aleksandra; Polten, Andreas; Ochocka, Renata; Dell'Italia, Louis; Bartoszewska, Sylwia; Króliczewski, Jarosław; Dąbrowski, Michał; Collawn, James F.
ABSTRACT: During hypoxia, a cellular adaptive response activates hypoxia‐inducible factors (HIFs; HIF‐1 and HIF‐2) that respond to low tissue‐oxygen levels and induce the expression of a number of genes that promote angiogenesis, energy metabolism, and cell survival. HIF‐1 and HIF‐2 regulate endothelial cell (EC) adaptation by activating genesignaling cascades that promote endothelial migration, growth, and differentiation. An HIF‐1 to HIF‐2 transition or switch governs this process from acute to prolonged hypoxia. In the present study, we evaluated the mechanisms governing the HIF switch in 10 different primary human ECs from different vascular beds during the early stages of hypoxia. The studies demonstrate that the switch from HIF‐1 to HIF‐2 constitutes a universal mechanism of cellular adaptation to hypoxic stress and that HIF1A and HIF2A mRNA stability differences contribute to HIF switch. Furthermore, using 4 genome‐wide mRNA expression arrays of HUVECs during normoxia and after 2, 8, and 16 h of hypoxia, we show using bioinformatics analyses that, although a number of genes appeared to be regulated exclusively by HIF‐1 or HIF‐2, the largest number of genes appeared to be regulated by both.—Bartoszewski, R., Moszynska, A., Serocki, M., Cabaj, A., Polten, A., Ochocka, R., Dell'Italia, L., Bartoszewska, S., Króliczewski, J., Dabrowski, M., Collawn, J. F. Primary endothelial cell–specific regulation of hypoxia‐inducible factor (HIF)‐1 and HIF‐2 and their target gene expression profiles during hypoxia. FASEB J. 33, 7929–7941 (2019). www.fasebj.org